Impact of targeted trainer feedback via video review on trainee performance of laparoscopic cholecystectomy. Issue 5 (October 2021) - O'Connell, Lauren; McKevitt, Kevin; Khan, Waqar; Waldron, Ronan; Khan, Iqbal; Barry, Kevin
Abstract: Introduction: Tools for improving operative performance for surgical trainees are increasingly desirable, particularly in the context of EWTD and 'run-through' training programmes. In addition, positive direct trainer feedback to trainees can improve skill acquisition and motivation, whilst negative feedback may have the opposite effect. 1 We aimed to examine the impact of targeted trainer feedback based on video analysis on trainee confidence and objective operative performance in laparoscopic cholecystectomy. Methods: Selected procedures designated as training cases were recorded. These were assessed by the trainers using the Independence-Scaled Procedural Assessment Score for laparoscopic cholecystectomy. Targeted feedback based on video review of selected procedures was then delivered by the trainers to the trainees. Trainees completed a self-reported questionnaire based on their response to this feedback. Subsequent to the feedback intervention, further training procedures were recorded and assessed. Results: A total of 6 trainees and 4 trainers participated in the study. For the pre-intervention assessment 15 cases were recorded, with a further 13 for the post-intervention assessment (total n = 28). The overall scores for the procedures performed post video feedback were improved, with a trend towards statistical significance (p = 0.08). However, there was a statistically significant improvement in the scores for performance of the triangle of Calot dissection after the feedback intervention (p = 0.009). The response rate to the questionnaire was 100%, with all trainees agreeing that they felt more confident and competent after the feedback intervention. Conclusion: Targeted feedback to trainees based on post-procedure video review improves trainee confidence and may also improve performance. ACGME Core Competencies; Patient Care and Procedural Skills; Practice Based Learning and Improvement. Highlights: Trainees agreed that feedback intervention improved their confidence and competence. Intervention produced significant improvement in more challenging procedural steps. May represent a useful tool to accelerate acquisition of laparoscopic skills.